Municipal Solid Waste Management under COVID-19: Challenges and Recommendations. Issue 6 (10th September 2020) - Vaverková, Magdalena Daria; Paleologos, Evan K; Dominijanni, Andrea; Koda, Eugeniusz; Tang, Chao-Sheng; Małgorzata, Wdowska; Li, Qi; Guarena, Nicolò; Mohamed, Abdel-Mohsen O; Vieira, Castorina S; Manassero, Mario; O'Kelly, Brendan C; et al.
Abstract : COVID-19 is proving to be an unprecedented disaster for human health, social contacts, and the economy worldwide. It is evident that the SARS-CoV-2 may spread through municipal solid waste (MSW), if collected, bagged, handled, transported, or disposed of inapproprately. Under the stress placed by the current pandemic on the sanitary performance across all MSW management (MSWM) chains, this industry needs to re-examine its infrastructure resilience with respect to all processes, from waste identification, classification, collection, separation, storage, transportation, recycling, treatment, and disposal. The current paper provides an overview of the severe challenges placed by COVID-19 onto MSW systems, highlighting the essential role of waste management (WM) in public health protection during the ongoing pandemic. It also discusses the measures issued by various international organisations and countries for protection of MSWM employees (MSWEs), identifying gaps, especially for developing countries, where personal protection equipment (PPE) and clear guidelines to MSWEs may not have been provided, and the general public may not be well informed. In countries with high recycling rates of MSW, the need to protect MSWEs' health has affected the supply stream of the recycling industry. The article concludes with recommendations for the MSW industry operating under public health crisis conditions.